The crucifixion and death of Jesus in Mark 15:21-41, from the perspective of its redaction history in the New Testament gospels - Hombana, Mphumezi (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.